Comparing Spiritual Narratives of Ibn Jubayr and Nizami - Muhammad Ihwan Safrudin; Muhammad Haidar Gibran; Aria Raizal Muhammad; Nurholis (Indo Publishing, 2025)
This comparative study analyzes the narrative and spiritual themes in two foundational works of Islamic literary tradition: A Pilgrimage to Mecca (a rihla or travelogue) by the 12th-century Andalusian scholar Ibn Jubayr, and Star-Crossed Lovers or Layla and Majnun (a masnavi or epic poem) by the Persian poet Nizami Ganjavi. Despite originating from different genres, languages, and purposes, one being a factual travel account and the other being an allegorical romance. Both masterpieces convergently explore the transformative journey of the human soul. Ibn Jubayr's work presents the physical Hajj as a profound spiritual pilgrimage. Through meticulous empirical observation of sacred sites and Muslim communities, his narrative transcends mere reportage to become a reflection on divine order, personal piety, and the unity of the Ummah. Conversely, Nizami's tragic tale of the